Analogy of lower and capital letters of vertical and italic handwriting in first grade literacy - Turan, Mehmet (My University, 2010)
This study has been carried out in order to determine the status of the analogy drawn with the capital and lower letters in vertical and italic handwriting by teachers working in the first grade classes of primary schools. The research has been conducted on 151 first grade teachers working in Turkey. The data was acquired by means of a questionnaire which was developed by the researcher. In data analysis process, SPSS program was utilized and frequencies, percentages and chi-square test were used. The research revealed that primary school teachers use following analogies: In capital letters, "glasses" for "B", "comb" for "E", "ladder" for "H", "handle of an umbrella" for "J", "snake" for "S" and "catapult" for "Y"; in italic handwriting, "crescent" for "C", "reverse of 3" for "E" and "mountain chain" for "M"; in lower letters, "glasses with a broken lens" for "b", "pipe wrench" for "f", "chair" for "h", "tunnel entrance" for "n" and "a glass" for "u"; "bent chair" for "h", "stick" for "l", "knob" for "p" and "duck" for "s". © 2010 Academic Journals.
Keywords: Analogy; First grade literacy; Letter analogy; Writing types